Leveraging antibiotic hormesis for cryptic natural product discovery - Joon Soo An; Ellysia N. Overton; Mohammad R. Seyedsayamdost (Proceedings of the National Academy of Sciences, 2026)
Microbial natural products are a foundational source of therapeutic agents, yet a vast majority remain inaccessible due to the limited expression of their biosynthetic gene clusters under standard laboratory conditions. To address this challenge, we developed a simple and broadly applicable screening approach based on the idea of antibiotic hormesis wherein high-dose growth-inhibitory antibiotics serve as low-dose elicitors of secondary metabolites. We generated an in-house library of all available clinical antibiotics and exposed nine phylogenetically diverse bacteria to high-dose growth inhibition and low-dose metabolite stimulation assays. The approach revealed the induction of cryptic metabolites with every strain tested. Four of these were selected for scale-up fermentation and comprehensive metabolomic analysis, leading to the identification of eight known but strain-novel cryptic metabolites and nine structurally unique, previously undescribed natural products. These findings underscore the utility of the antibiotic hormesis approach as a rapid and scalable platform for the discovery of natural products and therapeutic leads. Moreover, the consistent elicitation of cryptic metabolites highlights the generalizability of low-dose antibiotics as key signaling molecules in microbial metabolic regulation. Beyond expanding the repertoire of accessible natural products, this work lays the foundation for systematic studies into the molecular and ecological mechanisms that govern cryptic metabolite biosynthesis.